A study of distinctive features of Penang Hokkien in Malaysia. - Ng, Boon Sim (2013)
The main objective of the study is to explore distinctive words inherited from the Minnan source dialect. It is also aim to explore distinctive words created by the Hokkien community in the Northern region of Peninsular Malaysia. This study specifically seeks to identify the maintenance, changes and innovation in the Minnan dialect with reference to the use of existing distinctive words in Malaysian multilingual setting. The fieldwork involved a random selection of 12 native speakers of Hokkien from Penang and Kedah. A series of interviews and task- based discussions be carried out using qualitative approach. All collected spoken data will be transcribed into Minnan dialect for further analysis. Research findings showed that 160 distinctive words were shared between Penang Hokkien and the Minnan source dialect. Besides, there are 183 distinctive words originally created by the Malaysian Hokkien speakers due to the factors of language contact and cultural contact. This category of distinctive words is called “induced distinctive words” as it comprised of pure dialect creations and blending creations. This study presents a significant corpus for Chinese Dialectology as well as contribution to the area of cultural linguistics. In addition, the comparative study between the origin and the sub variety will add to the theory of historical linguistics and sociolinguistics.